1997
DOI: 10.1093/ajcn/65.5.1489
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant flavonols and ischemic heart disease in a Welsh population of men: the Caerphilly Study

Abstract: Antioxidant flavonols and their major food source, black tea, have been associated with a lower risk of ischemic heart disease (IHD) and stroke in Dutch men. We investigated whether flavonol intake predicted a lower rate of IHD in 1900 Welsh men aged 45-59 y, who were followed up for 14 y. Flavonol intake, mainly from tea to which milk is customarily added, was not related to IHD incidence [relative risk (RR), highest compared with lowest quartile: 1.0; 95% CI: 0.6, 1.6; P for trend = 0.996; n = 186] but was w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
265
2
8

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 464 publications
(285 citation statements)
references
References 16 publications
2
265
2
8
Order By: Relevance
“…The consumption of black tea in the United Kingdom is high compared with other countries (5±6 cups vs 1±2 cups per day) and yet the incidence of coronary heart disease is not lower. In contrast to earlier epidemiological data from The Netherlands (Hertog et al, 1993;Keli et al, 1996), where plain black tea is consumed, a recent study in the United Kingdom showed that consumption of tea with milk was not inversely associated with mortality of ischemic heart disease (Hertog et al, 1997). A possible explanation may be that the bioavailability of¯avonoids from tea is reduced by the addition of milk to black tea.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The consumption of black tea in the United Kingdom is high compared with other countries (5±6 cups vs 1±2 cups per day) and yet the incidence of coronary heart disease is not lower. In contrast to earlier epidemiological data from The Netherlands (Hertog et al, 1993;Keli et al, 1996), where plain black tea is consumed, a recent study in the United Kingdom showed that consumption of tea with milk was not inversely associated with mortality of ischemic heart disease (Hertog et al, 1997). A possible explanation may be that the bioavailability of¯avonoids from tea is reduced by the addition of milk to black tea.…”
Section: Introductionmentioning
confidence: 82%
“…Several epidemiological studies suggest that black tea consumption is associated with a reduced risk of degenerative diseases such as cardiovascular disease (Hertog et al, 1993;Keli et al, 1996). There is increasing evidence from experimental studies that free radical-mediated damage may play a role in the aetiology of cardiovascular disease and that antioxidants may act in preventing this damage (Steinberg et al, 1989;Witztum & Steinberg, 1991;Esterbauer & Ramos, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that addition of milk to tea, which is common practice in the United Kingdom, could explain the increased risk of death from isachemic heart disease associated with tea drinking in a Welsh population of heavy tea drinkers (Hertog et al, 1997b). Addition of milk to tea leads to binding of tea components to milk protein (Siebert et al, 1996) and may thus prevent their uptake by the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…In a Welsh population (United Kingdom) the consumption of tea was not associated with a lower mortality of ischaemic heart disease (Hertog et al, 1997b). Among heavy tea drinkers tea drinking was even related to an increased risk of death from ischaemic heart disease.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation